Ruta Turística para la comunidad de Ñamarin del cantón Saraguro, provincia de Loja - Yaguana Yaguana, Angelica Paulina (2018)
Tourism is an economic activity, where you can create products through the tourism offer of a certain sector, area or region, where you have natural and cultural attractions, and that associating them with other productive activities can help to diversify the economy of a population. One of these products are the Tourist Routes, which allow us to know the wealth of attractions that a sector has, helping its preservation and conservation, and at the same time propitiate a space of integration with nature and communities, in addition to corroborate with the health of people by exercising the walk, and decreasing environmental pollution. Ecuador is a tourist destination that has a great wealth of biodiversity, because it is located on the equatorial line in South America; that is, in both hemispheres, which allows it to have four regions: Costa, Sierra, Amazonia and Galápagos and where great natural and cultural wonders are found, so the increase in tourists has been remarkable during the last years. In the province of Loja, canton Saraguro is the community of Ñamarin, which has tourism potential both natural and cultural attractions, in addition to the customs and traditions inherited from the Saraguro culture. The community owns the wealth of scenic landscapes that are very important, so it was necessary to develop the research work for which goals were set within them, as is the general objective. "Design the Tourist Route for the community of Ñamarin of the canton Saraguro, province of Loja". Subsequently, three specific objectives were outlined, which are described below, the first objective; Make the tourist diagnosis of the cantonal head of Saraguro. For the fulfillment of the objective, the inductive, analytical deductive and synthetic methods were used, such as direct observation, interview, Tourism Diagnostic Matrix of Carla Ricaurte Quijano Communities, MINTUR tourist inventory cards of Ecuador, Ranking sheets of the Ministry of Tourism of the Ecuador (2017 methodology) and instruments and materials were also used, such as the Land Management Plan, as a complement to the collection of information, from the cantonal capital, and finally, the SWOT Matrix was applied to determine the current situation of the cantonal capital, the second objective; Prepare the Tourist Route for the Community of Ñamarin; to develop this objective, the inductive, analytical, synthetic and direct observation methods were used, as well as instruments such as GPS (GPS), to make the coordinates, altitude, travel time and distances, digital camera for digital support, for which the proposal was designed in the realization of a map that includes the location of the route, distances of each tourist attraction, and outstanding attractions of the tourist route. The elaboration of a file where the signage for the route is proposed according to the Information of the Corporate Manual of tourist signaling MINTUR, because this manual standardizes the signage in Ecuador, determining the pictograms of natural and cultural attractions, tourist activities, and The brand was also created, identifying the community and later the name of the route called "Hisikaka Machay Tourist 5 Route" and Slogan "An adventure for living" was raised. A script and itinerary of the route following the established order was also prepared. Once the Route was designed and planned, tourist product strategies were established, the triptych model, handbag, and the publication on the GAD website of Saraguro were designed; the Third Objective; Socialize the results of the research work; In order to carry out the socialization of the results obtained, the MARPP technique was applied, which allowed for socialization through the participation of the authorities and the community involved. Finally the